The impact of climate on raising livestock animals in Aleppo governorate - عساني ندى; إبراهيم سعيد (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The study concludes about the effect of the two most important The livestock sector has avital role in achieving many sustainable development Goals, as it has a role in supporting livelihoods contributing, to raising national income and contributing to healthy, diets this sector is affected by the natural and human factors prevailing areas where it is raised especially the various climate elements, which its impact may be direct or indirect in this research, the different climate element (solar radiation, temperature, rainfall, relative humidity and wind), in Aleppo governorate and impact of these element on raising livestock number( sheep, goats and cow) between( 2001 and 2021 ), a study of density and distribution across the regions of the governorate, showed through the study that livestock breeding is widespread in all regions of the governorate, but in different number depending on the differences in climatic and environmental condition in each region, there are approximately (2733011), heads of animals in the governorate in (2021), and it reached the number of sheep was (2356006) head in (2021) which is approximately (86,2%) of the total livestock, and the number goats was (236652) heads at the rate of (8.6%), as for cows and calves they come in third places.